Epitaxial growth and magnetic properties of Fe nanowedge islands on Mo(110) - SHVETS, IGOR; MURPHY, SHANE; USOV, VICTOR (My University, 2005)
Fe films with a nominal thickness greater than or equal to 2 Angstrom grown on Mo(1 10) at 500 less than or equal to Tless than or equal to 750 K self-assemble into nanowedge islands supported on a pseudomorphic Fe wetting layer. We discuss mechanisms that contribute to the island growth and distribution. Fe adatoms migrate towards the islands under the influence of the strain induced in the substrate around each island and subsequently enter the island through a vertical climb mechanism. We demonstrate that the magnetic properties of these nanostructures are governed by their shape and do not display the in-plane spin reorientation transition found in the morphologically similar Fe/W(1 1 0) system.
PUBLISHED
Proceedings of the 5th International Symposium on Metallic Multilayers
Keywords: self-assembly; iron; molybdenum; STM; Atomic, molecular and chemical physics